The Significance of Supervision in Enhancing the Quality of Guidance and Counseling in Schools - Muhammad Ridho Albari; Uman Suherman; Setiawati Setiawati (Journal of Education and Counseling (JECO), 2024)
The implementation of guidance and counseling supervision in Indonesia is still lacking attention and there are few instances of its implementation. However, supervision is one of the platforms for developing the competencies of guidance and counseling teachers in delivering counseling services. Therefore, this study aims to provide an understanding of the importance of implementing guidance and counseling supervision to develop the competencies of guidance and counseling teachers. The research method used is a literature review, to determine how guidance and counseling supervision have been implemented in previous studies and identify the obstacles faced. The results of this study indicate that many schools still overlook the implementation of supervision, there are several obstacles to implementing supervision, and there are recommended approaches for conducting supervision.